Effect of Enhanced Recovery After Surgery on Postoperative Recovery and Quality of Life in Patients Undergoing Laparoscopic Partial Nephrectomy - Miao, Chenkui; Yu, Aimei; Yuan, Han; Gu, Min; Wang, Zengjun (Frontiers in Oncology, 2020)
Patients who underwent laparoscopic partial nephrectomy from the First Affiliated Hospital of Nanjing Medical University from May 2016 to May 2019 were randomly divided into ERAS and control group. The clinical indicators, preoperative and postoperative anxiety, depression and postoperative quality of life were compared between the two groups. The recovery time, hospitalization cost, incidence of complications and postoperative anxiety of patients in ERAS group was lower than that of the control group. The satisfaction during hospitalization, scores of physical function, role function, emotional function and general health status of the ERAS group was also significantly increased. Applying the ERAS to patients undergoing laparoscopic partial nephrectomy can improve their prognosis, experience of medical treatment and life quality after surgery as well as have certain economic advantages.